Teacher Efficacy and Commitment in Teaching Arabic: A Correlational Study - Mohamed Adnan, Mohamad Azrien; Mamat, Arifin; Ibrahim, Mohd Burhan; Ahmed Mohamed, Ismaiel Hassanein (Centro de Investigaciones en Ciencias Sociales y Humanidades desde America Latina, 2019)
Teacher efficacy researches have been widely examined by many researchers in various context and subject areas. Yet, in the field of Teaching Arabic as a Foreign Language (TAFL) , the investigation into teacher's efficacy and its relation to their commitment is extremely uncommon. Therefore, the current study explores the validity and reliability of the instrument used in assessing teacher's efficacy in teaching Arabic and also their commitment to teaching. The study also examined Arabic teaching efficacy in relation to teacher commitment. The current study involved 252 teachers out of 487 teachers from 57 National Religious Secondary Schools throughout Malaysia. A structural equation modelling with AMOS was employed to investigate the effects of hypotheses model. Confirmatory factor analysis supported the adequacy of the constructs of teacher efficacy and teacher commitment and found that the two constructs were multidimensional constructs with four underlying dimension respectively. The findings also showed that teacher efficacy influence teacher commitment. Several essential theoretical implications for developing and enhancing teachers in the Malaysian Secondary Arabic education context have arisen from the current study.